Positron emission tomography/computed tomography manifestations of primary hepatic myxoid liposarcoma: A case report. Issue 39 (September 2018) - Liu, Weihai; Liang, Wenjie; Peng, Zhiyi
Abstract: Rationale: Computed tomography (CT) and magnetic resonance imaging (MRI) are conventional used to evaluate liver tumors. Detection of fat component is considered an important clue to the imaging diagnosis of hepatic myxoid liposarcoma. However, the positron emission tomography (PET)/CT report of hepatic myxoid liposarcoma is scarce, and the metabolic characteristics of primary hepatic myxoid liposarcoma are still unknown. Patient Concerns: In this report, we report the PET/CT manifestations of a rare case of primary hepatic myxoid liposarcoma that was confirmed by pathologic examination. A 29-year-old male patient presented with a nodule adjacent to the umbilicus that had been present for 2 weeks. PET/CT showed a hypoattenuating mass with moderate uptake (maximum standardized uptake value [SUVmax] 1.9), except for a slightly hyperattenuating focal area with intense uptake (SUVmax 3.1). Diagnoses: The final pathologic diagnosis was confirmed, by means of laparotomy, to be a primary hepatic myxoid liposarcoma with multiple extrahepatic metastases. Interventions: The lesions in the left liver and periumbilical abdominal wall were punctured. During the laparotomy, hepatic malignant tumors were confirmed and metastasized widely in the abdominal cavity. Outcomes: An abdominal CT performed 4 months after initial presentation showed extensive metastasis. Lessons: Primary hepatic myxoid liposarcoma may manifest as moderate metabolism with less fat on PET/CT. PET/CT is not only valuable in reflecting the round cell component of hepatic myxoid liposarcoma, but also in estimating its origin.